Superficieibacter electus gen. nov., sp. nov., an Extended-Spectrum β-Lactamase Possessing Member of the Enterobacteriaceae Family, Isolated From Intensive Care Unit Surfaces - Potter, Robert F.; D'Souza, Alaric W.; Wallace, Meghan A.; Shupe, Angela; Patel, Sanket; Gul, Danish; Kwon, Jennie H.; Beatty, Wandy; Andleeb, Saadia; Burnham, Carey-Ann D.; Dantas, Gautam (Frontiers in Microbiology, 2018)
Two Gram-negative bacilli strains, designated BP-1(T) and BP-2, were recovered from two different Intensive Care Unit surfaces during a longitudinal survey in Pakistan. Both strains were unidentified using the bioMerieux VITEK MS IVD v2.3.3 and Bruker BioTyper MALDI-TOF mass spectrometry platforms. To more precisely determine the taxonomic identity of BP-1(T) and BP-2, we employed a biochemical and phylogenomic approach. The 16S rRNA gene sequence of strain BP-1(T) had the highest identity to Citrobacter farmeri CDC 2991-81(T) (98.63%) Citrobacter amalonaticus CECT 863(T) (98.56%), Citrobacter sedlakii NBRC 105722(T) (97.74%) and Citrobacter rodentium NBRC 105723(T) (97.74%). The biochemical utilization scheme of BP-1(T) using the Analytic Profile Index for Enterobacteriaceae (API20E) indicated its enzymatic functions are unique within the Enterobacteriaceae but most closely resemble Kluyvera spp., Enterobacter cloacae and Citrobacter koseri/farmeri. Phylogenomic analysis of the shared genes between BP-1(T), BP-2 and type strains from Kluyvera, Citrobacter, Escherichia, Salmonella, Kosakonia, Siccibacter and Shigella indicate that BP-1(T) and BP-2 isolates form a distinct branch from these genera. Average Nucleotide Identity analysis indicates that BP-1(T) and BP-2 are the same species. The biochemical and phylogenomic analysis indicate strains BP-1(T) and BP-2 represent a novel species from a new genus within the Enterobacteriaceae family, for which the name Superficieibacter electus gen. nov., sp. nov., is proposed. The type strain is BP-1(T) (= ATCC BAA-2937, = NBRC 113412).